A rationally designed cancer vaccine based on NIR-II fluorescence image-guided light-triggered remote control of antigen cross-presentation and autophagy - Aihua Wu; Afeng Yang; Qinli Tong; Guoguang Wei; Sihang Zhang; Sheng Yu; Chen Zhang; Jiaojiao Xu; Wei Lu (Elsevier, 2023)
Cancer vaccines represent a promising immunotherapeutic treatment modality. The promotion of cross-presentation of extracellular tumor-associated antigens on the major histocompatibility complex (MHC) class I molecules and dendritic cell maturation at the appropriate time and place is crucial for cancer vaccines to prime cytolytic T cell response with reduced side effects. Current vaccination strategies, however, are not able to achieve the spatiotemporal control of antigen cross-presentation. Here, we report a liposomal vaccine loading the second near-infrared window (NIR-II, 1000-1700 nm) fluorophore BPBBT with an efficient photothermal conversion effect that offers an NIR-light-triggered endolysosomal escape under the imaging guidance. The NIR-II image-guided vaccination strategy specifically controls the cytosolic delivery of antigens for cross-presentation in the draining lymph nodes (DLNs). Moreover, the photothermally induced endolysosomal rupture initiates autophagy. We also find that the adjuvant simvastatin acts as an autophagy activator through inhibiting the PI3K/AKT/mTOR pathway. The light-induced autophagy in the DLNs together with simvastatin treatment cooperatively increase MHC class II expression by activating autophagy machinery for dendritic cell maturation. This study presents a paradigm of NIR-II image-guided light-triggered vaccination. The approach for remote control of antigen cross-presentation and autophagy represents a new strategy for vaccine development.